Peran Wilayatul Hisbah dalam Implementasi Qanun Aceh Nomor 11 Tahun 2002 di Aceh Besar - Muhammad Riski Renaldi; Bukhari Ali; T.Surya Reza (Journal of Innovative and Creativity, 2026)
The Role of Wilayatul Hisbah in the implementation of Number 11 of 2002 Concerning the Implementation of Islamic Sharia in the Field of Aqidah, Worship and Islamic Propagation in Aceh Besar, with a focus on the implementation of legal norms that regulate the order of community worship, especially the regulation of congregational prayers and the cessation of activities during prayer times. This study uses a juridical-empirical method with a conceptual and legislative approach, and is analyzed descriptively-analytical. Data were obtained through literature studies, field observations, and interviews with Wilayatul Hisbah officers and community leaders in Aceh Besar Regency. The results of the study indicate that the role of wilayatul hisbah in enforcing sharia, especially the development and protection of Aqidah, has not been implemented well, where Qanun Number 11 of 2002 should be the best solution for the implementation of Islamic Sharia through routine patrols, direct appeals, and action against violations such as continuing activities, opening businesses, or conducting economic activities when the call to prayer sounds until the prayer is finished. However, awareness of some people to comply with these regulations is still low. Therefore, it is necessary to strengthen coordination between the regional government, Wilayatul Hisbah, and religious leaders so that the implementation of the qanun can be carried out consistently and effectively, while at the same time raising a shared awareness of the importance of respecting prayer times as part of orderly worship in Aceh Besar